Little Bird [videorecording (DVD)] - Podemski, Jennifer; Moscovitch, Hannah (PBS Distribution, 2023)
In 1968, five-year-old Bezhig Little Bird was forcibly removed from Long Pine Reserve and adopted into a Jewish family in Montreal, and renamed Esther Rosenblum. Eighteen years later, she embarks on a journey to unravel her history.